Environmental Risk Factors and Congenital Heart Disease: An Umbrella Review of 165 Systematic Reviews and Meta-Analyses With More Than 120 Million Participants - Zhang, Tie-Ning; Wu, Qi-Jun; Liu, Ya-Shu; Lv, Jia-Le; Sun, Hui; Chang, Qing; Liu, Chun-Feng; Zhao, Yu-Hong (Frontiers in Cardiovascular Medicine, 2021)
Background The etiology of congenital heart disease (CHD) has been extensively studied in the past decades. Therefore, it is critical to clarify clear hierarchies of evidence between types of environmental factors and CHD. Methods Electronic searches in PubMed, Embase, Web of Science, Cochrane database were conducted from inception to April 20, 2020 for meta-analyses investigating the aforementioned topic (PROSPERO CRD42020193381). Results Overall, 41 studies including a total of 165 meta-analyses of different environmental factors and CHD were examined, covering a wide range of risk factors. The summary random effects estimates were significant at P values less than 0.05 in 63 meta-analyses (38%), and 15 associations (9%) were significant at P values <10-6. Of these meta-analyses, eventually one risk factor (severe obesity; relative risk: 1.38, 95% confidence interval: 1.30 to 1.47) had significant summary associations at P <10-6, included more than 1000 cases, had 95% prediction intervals excluding the null value, and were not suggestive of large heterogeneity (I²<50%), small-study effects (P value for Egger’s test >0.10), or excess significance (P >0.10). Eight associations (5%) (including maternal lithium exposure, maternal obesity, maternal alcohol consumption, and maternal fever) had results that were significant at P <10-6, included more than 1000 cases, and had 95% prediction intervals excluding the null value (highly suggestive). Conclusion This umbrella review shows that many environmental factors have substantial evidence in relation to the risk of developing CHD. More and better-designed studies are needed to establish robust evidence between environmental factors and CHD.